Gait velocity as a tool for evaluating the effects of gait training in patients with chronic stroke - Guzik, Agnieszka; Drużbicki, Mariusz; Kwolek, Andrzej; Przysada, Grzegorz; Brzozowska-Magoń, Agnieszka (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Background. Gait velocity is a simple but very essential parameter which may be applied as an indicator of functional efficiency. Gait of stroke patients is characterized by reduced speed. As a result, the patients have significantly limited functioning capabilities, including walking independently outside home. The study was designed to assess selected temporal gait parameters, including gait velocity, stride velocity and swing phase velocity in patients with chronic stroke following a rehabilitation program with the use treadmill. Material and method. The study was conducted in a group of 50 patients with hemiparesis in the late period after stroke. Temporal gait parameters such as: gait velocity, stride velocity and swing velocity were examined. Additionally, 10-metre walk test was measured. Results. While analyzing 10-metre walk test results it was shown that after rehabilitation gait velocity increased by an average of 0.15 m/s (p = 0.0000). Similar results were obtained in terms of gait velocity which had been assessed using a 3-dimensional gait analysis, the average gait velocity increased by 0,14m/s (p = 0.0000). Analyzing stride velocity, both the paretic and non-paretic side it was noted that after rehabilitation this particular parameter increased by an average of 0.05 m/s (p = 0.0019) and 0.06 m/s (p = 0.0052). Similar results were achieved in terms of swing velocity of the paretic side - p = 0.0017. Conclusions. It was demonstrated that rehabilitation program with the use of treadmill enabled significant improvement in gait velocity, stride velocity and swing phase velocity in patients with chronic stroke. Gait velocity is a practical and simple tool to be applied for monitoring of progress in rehabilitation and for assessing effects of gait re-education in patients with hemiplegia in a chronic stage after stroke.

Wstęp. Prędkość chodu jest prostym, a zarazem bardzo istotnym parametrem, który może być stosowany jako wyznacznik sprawności funkcjonalnej. Chód pacjentów po udarze mózgu charakteryzuje się zmniejszoną prędkością. W efekcie pacjenci mają znacznie ograniczone możliwości funkcjonowania, w tym samodzielnego chodu poza domem. Celem pracy jest ocena wybranych czasowych parametrów chodu, w tym prędkości chodu, prędkości cyklu chodu oraz prędkości fazy przenoszenia u pacjentów w okresie późnym po udarze mózgu, po programie rehabilitacji z wykorzystaniem bieżni ruchomej. Materiał i metoda. Badanie przeprowadzono w grupie 50 pacjentów z niedowładem połowiczym w okresie późnym po udarze mózgu. Analizowano czasowe parametry chodu: prędkość chodu, prędkości cyklu chodu oraz prędkości fazy przenoszenia. Dodatkowo wykonano test drogi na 10 metrach. Wyniki. Analizując wyniki testu drogi wykazano, że po zakończeniu programu rehabilitacji prędkość chodu wzrosła średnio o 0,15 m/s (p = 0,0000). Podobne wyniki uzyskano w zakresie prędkości chodu ocenionej z wykorzystaniem 3-wymiarowej analizy chodu, średnia prędkość chodu wzrosła o 0,14m/s (p = 0,0000). Analizując prędkość cyklu chodu zarówno po stronie niedowładnej jak i zdrowej zanotowano, iż w wyniku rehabilitacji nastąpił wzrost tego parametru średnio o 0,05 m/s (p = 0,0019) i 0,06 m/s (p = 0,0052). Zbliżone wyniki uzyskano również w zakresie prędkości fazy przenoszenia po stronie niedowładnej – p = 0,0017. Wnioski. Program rehabilitacji z wykorzystaniem bieżni ruchomej wpłynął na istotną poprawę w zakresie prędkości chodu, prędkości cyklu chodu oraz prędkości fazy przenoszenia u pacjentów w okresie późnym po udarze mózgu. Prędkość chodu jest przydatnym narzędziem umożliwiającym ocenę efektów reedukacji chodu pacjentów z niedowładem połowiczym w okresie późnym po udarze mózgu.
Prędkość chodu jako narzędzie oceny efektów treningu chodu u pacjentów w okresie późnym po udarze mózgu
Keywords: stroke; gait; gait velocity; treadmill training; udar mózgu; chód; prędkość chodu; trening na bieżni